👤

1.√2y² -√18y-√8y²+√32y=(√2y²-√8y²)-(-√18y+√32y)=
2.(x+3)(x-2)-x²+5=
3.(x-4)(x+1)-(x+2)(x+1)=
4.(2√3x+√2)(√2x-√3)-2√6x²=
5.(√5x+1)(√5x+2)-(√5-2)(√5-1)=



Răspuns :

1) [tex]( \sqrt{2}y ^{2}-2 \sqrt{2} y^{2} )+3 \sqrt{2}y+4 \sqrt{2}y= - \sqrt{2} y^{2}+7 \sqrt{2}y [/tex]
2) [tex] x^{2} -2x+3x-6- x^{2} +5=x-1[/tex]
3) [tex] x^{2} +x-4x+4- x^{2} -x-2x-2=-6x-2[/tex]
4)[tex]2 \sqrt{6} x^{2} -6x+2x- \sqrt{6} -2 \sqrt{6} x^{2} =-4x- \sqrt{6} [/tex]
5)[tex]5 x^{2} +2 \sqrt{5}x+ \sqrt{5}x +2-(5- \sqrt{5}-2 \sqrt{5}+2 ) [/tex][tex]=5 x^{2} +3 \sqrt{5}+2-7+ \sqrt{5}+3 \sqrt{5}=5 x^{2} +7 \sqrt{5}-5 [/tex]